In utero defecation: a new concept - Çiftçi, Arbay Ö.; Tanyel, F. Cahit (The Turkish Journal of Pediatrics, 1998)
According to the current concepts, the human fetus does not defecate, and passage of meconium into the amniotic fluid is an indicator of fetal distress. However, the literature consists of reports in which fetal defecation is postulated to be a physiologic event. In light of these reports and our observations, we have developed the hypothesis that fetal defecation is a physiologic event independent from fetal distress and associated with a clearance mechanism of the amniotic fluid. This hypothesis has been proved by a series of experimental studies. We have shown that goat fetuses defecate the contrast medium into the amniotic cavity in the absence of fetal distress. We have clearly demonstrated for the first time the transport of radioactive meconium through the gastrointestinal tract into the amniotic fluid by using a radiopharmaceutical agent. It is known that the clearance mechanism of the amniotic fluid is supressed under fetal distress conditions. We suggest that meconium stained amniotic fluid is not related to meconium passage due to fetal distress; rather, it reflects impaired clearance of amniotic fluid containing meconium because of physiologic in utero defecation. This is discussed in detail with a review of the literature.